2020
DOI: 10.1007/s11104-020-04723-w
|View full text |Cite
|
Sign up to set email alerts
|

Root growth and presence of Rhizophagus irregularis distinctly alter substrate hydraulic properties in a model system with Medicago truncatula

Abstract: Aim We investigated how substrate hydraulic properties respond to the presence of arbuscular mycorrhizal fungi (AMF) in root-containing and root-free substrate zones in a Medicago truncatula-Rhizophagus irregularis model system. Methods Before planting, two compartments constructed from standard soil sampling cores (250 cm3) were implanted into non-mycorrhizal and mycorrhizal pots containing a sand-zeolite-soil mix. One compartment allowed roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 113 publications
2
5
0
Order By: Relevance
“…On the other hand, AMF presence in the WT facilitated higher leaf water potential despite declining soil water potential ( Figure 3 ). AMF could play a central role in sustaining the hydraulic continuity between root and soil, as it not only improves the unsaturated hydraulic conductivity ( Bitterlich et al, 2018a ; Pauwels et al, 2020 ), but also avoids excessive drop of soil water potential around roots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, AMF presence in the WT facilitated higher leaf water potential despite declining soil water potential ( Figure 3 ). AMF could play a central role in sustaining the hydraulic continuity between root and soil, as it not only improves the unsaturated hydraulic conductivity ( Bitterlich et al, 2018a ; Pauwels et al, 2020 ), but also avoids excessive drop of soil water potential around roots.…”
Section: Resultsmentioning
confidence: 99%
“…In maize, Quiroga et al (2019) reported that AMF symbiosis enabled higher stomatal conductance under soil water deficit. Furthermore, it was also suggested that AMF increase root hydraulic conductivity ( Aroca et al, 2007 ; Quiroga et al, 2019 ) and alter soil hydraulic properties ( Bitterlich et al, 2018a ; Pauwels et al, 2020 ). However, the impact of AMF on soil-plant hydraulic conductance, especially in drying soil, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The substrate matric potential increased with the degree of drought stress. The effects of AMF on the matric potential have already been described in tomato ( Solanum lycopersicum L.) [ 40 ], rice ( Oryza sativa L.) [ 41 ], barrel clover ( Medicago truncatula ) [ 42 , 43 ], and wheat ( Triticum aestivum ) [ 44 ] crops. Bitterlich et al [ 40 ] reported that S. lycopersicum plants inoculated with 72,500 spores of Rhizoglomus irregulare per plant had a water retention tolerance between –3 and –6 kPa.…”
Section: Discussionmentioning
confidence: 99%
“…AQP is considered to be involved in diverse physiological mechanisms that determine the pattern as well as the rate of plant water usage ( Vadez et al, 2013 ). Further AMF also enhanced the root hydraulic conductance and maintains hydraulic continuity between plant roots thereby reducing the drop in matric potential at the root-soil furnace and enhancing the water uptake by AMA inoculated plants ( Quiroga et al, 2019a ; Pauwels et al, 2020 ; Abdalla and Ahmed, 2021 ).…”
Section: Arbuscular Mycorrhizal Fungi Regulates Gene Expression Aquap...mentioning
confidence: 99%